The three amigos : The transnational filmmaking of Guillermo del Toro, Alejandro González Iñárritu, and Alfonso Cuarón - Shaw, Deborah (Book collections on Project MUSE., 2013)
"This is the first academic book dedicated to the filmmaking of the Mexican born directors, Guillermo del Toro, Alejandro González Iñárritu, and Alfonso Cuarón. The book examines the career trajectories of the directors and presents a detailed analysis of their most significant films. These include studies on del Toro's Cronos/Chronos, El laberinto del fauno/Pan's Labyrinth and Hellboy II: The Golden Army; Inárritu's Amores Perros, 21 Grams and Babel; and Cuarón's Sólo con tu pareja/Love in the Time of Hysteria, Y tu mamá tambien, and Children of Men."--Page 4 of cover.